Relationship between belief factors with the teenagers' acceptance of the newspapers - Ahmad Ghazali, Akmar Hayati; Omar, Siti Zobidah; Bolong, Jusang; Mansor, Nor Shahila (2013)
Newspaper contains abundance of information which enables to enhance the teenagers’ knowledge. Nevertheless, in the current situation, the teenagers’ acceptance of newspaper is declining due to the lack of interest in reading this kind of medium. This situation is alarming especially in supporting the Malaysian government aspirations to create a knowledgeable society by the year 2020. Looking at this scenario, the objective of this study is to investigate the relationship between belief factors with the teenagers’ acceptance of the newspapers. Specifically, this research aims to identify the types of news which are chosen by teenagers and the influence of the belief factors towards the teenagers’ acceptance of the newspaper. This study focuses on teenagers since this group encompasses the majority of the Malaysian population. The instrument used in this study is based on Measuring the Concept of Credibility developed by Gaziano dan McGrath (1986), and Trust in News Media developed by Kohring and Matthes (2007). Using a quantitative approach, a total of 387 teenagers from 4,501 population were selected to be the respondents of this study. The data was analyzed using Statistical Package for Social Science (SPSS) version 18.0. The results shows that entertainment news seem to be the teenagers’ most preferences. At the same time, newspaper is accepted by the teenagers due to their belief factor in the newspaper reporting such as social concern, selection of topics, selection of facts and assessment of reporter. In conclusion, it is hoped that the results of this study will be able to assist the newspaper institutions to publish contents related to education and knowledge. So that the newspapers could be one of the leading learning references apart from the school textbooks and printed references in order to fulfill the various needs of the teenagers.